The Effect of Chronic Administration of Buspirone on 6-Hydroxydopamine-Induced Catalepsy in Rats - Hamdolah Sharifi (Advanced Pharmaceutical Bulletin, 2012)
Purpose: Several evidences show that serotonergic neurons play a role in the regulation of movements executed by the basal ganglia. Recently we have reported that single dose of buspirone improved 6-hydroxydopamine (6-OHDA) and haloperidol-induced catalepsy. This study is aimed to investigate effect of chronic intraperitoneal (i.p.) administration of buspirone on 6-OHDA-induced catalepsy in male Wistar rats. Methods: Catalepsy was induced by unilateral infusion of 6-OHDA (8 μg/2 μl/rat) into the central region of the SNc and was assayed by the bar-test method 5, 60, 120 and 180 min after drugs administration in 10th day. The effect of buspirone (0.5, 1 and 2 mg/kg, i.p. for 10 days) was assessed in 6-OHDA-lesioned rats. Results: The results showed that chronic injection of buspirone (0.5, 1 and 2 mg/kg, i.p. for 10 days) decreased catalepsy when compared with the control group. The best anticataleptic effect was observed at the dose of 1 mg/kg. The catalepsy-improving effect of buspirone was reversed by 1-(2-methoxyphenyl)- 4-[4-(2-phthalimido) butyl]piperazine hydrobromide (NAN-190), 0.5 mg/kg, i.p.,as a 5-HT1A receptor antagonist. Conclusion: Our study indicates that chronic administration of buspirone improves catalepsy in a 6-OHDA-induced animal model of parkinson's disease (PD). We also suggest that buspirone may be used as an adjuvant therapy to increase effectiveness of antiparkinsonian drugs. In order to prove this hypothesis, further clinical studies should be done.